The Correlation Between Reading Anxiety and Reading Comprehension Achievement of The Eleven Grade Student of SMA Negeri 1 Muara Badak - Ameliah, Usnur; Khatimah, Khusnul (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This study aims to examine the influence of students’ reading anxiety and students’ reading comprehension on eleventh grade students at SMA Negeri 1 Muara Badak. The dependent variable in this research is reading comprehension while the independent variable is reading anxiety. This research was conducted on class XI students of SMA Negeri 1 Muara Badak, with total 60 respondents. This research used quantitative method. Data collection was carried out using a questionnaire by testing students' reading anxiety and students' reading comprehension. Multiple regression analysis techniques using SPSS 27 (Statistical Product and Service Solution 27) are used to analyze the data. The results of this research showed several conclusions that can be conveyed. First, reading anxiety for all students provides a significant correlation to their reading comprehension achievement with r 0.896. This can be seen in the high level of correlation. It can be proven that different levels of reading anxiety have a significant influence on students' achievement of reading comprehension. Second, it can be concluded that students' reading anxiety has a significant influence on students' reading comprehension achievement. This showed that one of the psychological factors, namely reading anxiety, has an important contribution to the success of students' reading achievement. This research may have some pedagogical implications for future researchers and students.